Review of time in therapeutic range of warfarin in a tertiary centre in Malaysia - Gan, K.X.; Chung, B.K.; Sim, K.Y.; Tan, J.E.; Lian, Z.Y.; Chan, En Ze; Ling, H.S. (Elsevier, 2021)
Anticoagulation management is a recognized challenge in medical care. Complications of supratherapeutic anticoagulation are hemorrhagic stroke, major bleeding, and death. There is an even greater risk of ischemic stroke in AF, worsening of VTE associated with subtherapeutic dosing.